Math, asked by panwaraakash0007, 1 year ago

Simplify (√11 - √7) / (√11 + √7)
plz anwer fast.

: (​

Answers

Answered by snehakumari4534581
1

Answer:

(√11 - √7) / (√11 + √7)

after rationalising the above term......we get

= (√11 - √7) / (√11 + √7) × (✓11 - ✓7) / (✓11 - ✓7)

=(√11 - √7) ^2/ (√11 + √7) (✓11 - ✓7)

=(✓11)^2-2×✓11×✓7+(✓7)^2/(✓11)^2-(✓7)^2

=11-2✓77+7/11-7

=18-2✓77/4

=2(9-✓77)/4

=9-✓77/2

hope it helps you

Answered by ThinkingBoy
1

\frac{\sqrt{11}-\sqrt{7}  }{\sqrt{11}+\sqrt{7}}

= \frac{(\sqrt{11}-\sqrt{7})(\sqrt{11}-\sqrt{7})}{(\sqrt{11}+\sqrt{7})(\sqrt{11}-\sqrt{7})}

= \frac{11+7-2\sqrt{77} }{11-7}

=\frac{18-2\sqrt{77} }{4}

=\frac{9-\sqrt{77} }{2}

Similar questions